Pengaruh Pemberian Ekstrak Daun Sirih Merah (Piper Crocatum) Terhadap Penurunan Kadar Gula Darah - Paizer, Dindi; Apriani, Dwi; Syafitri, Ria Dila (JURNAL KESEHATAN TERAPAN, 2022)
Diabetes Mellitus is a disease that occurs due to the inability of the pancreas gland to produce sufficient insulin or when the human body is not able to optimally use the insulin that has been produced by the pancreas gland. In treating diabetes mellitus, apart from using drugs, it can also be therapeutic, such as the use of red betel leaf boiled water. The purpose of this study was to determine the effect of boiled red betel leaf (Piper Crocatum) on lowering blood glucose levels. This study is a literature study conducted by making a summary and analysis of existing articles or research. The results of the analysis of the 5 journals carried out showed that there was an effect of giving red betel leaf extract (Piper crocatum) on lowering blood glucose levels in Diabetes Mellitus patients. The conclusion of this study is that giving 3 pieces of betel leaf decoction with 3 cups of boiled water up to half a cup or with a dose of 0.078 gr / 20 gr of body weight can reduce blood sugar levels. Keywords: Red Betel Leaf, Diabetes Mellitus, Blood Sugar Level